Case report: Primary Ewing sarcoma of the ureter, an exceptional finding of unique manifestation of disease - Valeri, Marina; Dore, Leocadia; Rudini, Noemi; Cieri, Miriam; Elefante, Grazia Maria; Saita, Alberto; Bertuzzi, Alexia; Colombo, Piergiuseppe (Frontiers in Oncology, 2023)
Ewing sarcoma (ES) is the second most common malignant bone tumor in children and has also been described in adults with highly aggressive behavior. ES belongs to the small round blue cell tumor family and presents the distinctive translocation of FET-ETS family genes (85% with EWSR1), generating gene fusions. Extraskeletal ES mainly occurs in soft tissues; the urogenital tract is rarely affected, and ureteral localization is an exceptional event with only 4 cases described in the literature. Here we report the first Italian case of primary ES of the ureter, a 24-year-old young man with lower back pain and a narrowed left ureteral lumen on CT scan. ES of the urogenital tract is an almost unique condition with a nonspecific clinical presentation and a challenging diagnosis for pathologists. We encourage awareness of these exceptional events in the differential diagnosis of ureteral lesions in young patients.